Traditional cereal processing technologies and their importance to African communities: A review - Benhura, Chakare; Mushonga, Nyasha G; Muguse, Amanda; Kamunhukamwe, Kudzai; Mpezani, Clareta; Chibira, Lisa; Taruvinga, Mellisa; Patel, Santa M (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Traditional cereal technologies have long been applied in Africa since the dawn of time. Cereal technology is the processing of cereal grain into starch and other nutrients for consumption by humans or animals. The technology involves all processes that the grain is taken through from the farm till it reaches the table for consumption. Examples of traditional cereal technologies employed are sun drying, parboiling, roasting, malting and fermentation. Poor livelihoods and inadequate nutritious foods for some African communities may be alleviated through use of the indigenous cereal technologies. The objective of this review is to discuss various traditional cereal technologies and explain their influence on the life of communities. This review is based on traditional cereal technologies that have been employed over the years and their importance to the livelihood of communities in Africa. Technologies employed by various communities and how they have paved way for the development of current technologies were explored. Information in the review was extracted from various journals and papers on cereal technologies. Some of the information was obtained from different rural communities thereby giving details of technologies being employed todate. The techniques used are an effective way of improving nutritional quality, reducing anti-nutritive compounds and improving the functionality of cereals. Traditional cereal technologies improve sensory properties and shelf life of foods. The technologies are also important in reducing post-harvest food losses and increasing food availability. As reviewed, these technologies bring variety to diets and increase the bioavailability of some nutrients, serve as a source of income and encourage unity in communities. By creating employment opportunities in rural areas, use of traditional cereal technologies contribute to reduction of rural-urban migration. Cereal processing technologies are an important part of community livelihoods, food and nutrition security especially in rural areas. However, there is need to continuously improve some of these techniques to ensure sustainability of livelihoods and food security.